Splendors of Latin cinema - Hernández Rodríguez, Rafael, 1963- (Non-Series., 2010)
In this insightful account, R. Hernandez-Rodriguez analyzes some of the most important, fascinating, and popular films to come out of Latin America in the last three decades, connecting them to a long tradition of filmmaking that goes back to the beginning of the 20th century.